Pursuing a Career in Translation for Indonesian Speakers - Michael Alfredo Pesurnay; Sisilia Endah Lestari; Wasisti Argo Tyas Reno; Barli Bram (Indonesian Journal of English Language Studies (IJELS), 2016)
Since becoming a translator needs certain skills and qualifications, this article provides detailed information on the process from starting and developing a career in translation. Based on accessible references and a limited interview with a professional translator, some recommendations are in place. A perspective translator has to go through the following procedures; (1) acquisition and development of language competence, (2) translation competence development, (3) translation market, and (4) career development. Being a successful translator, one should have known how to start, including how to tell people their existence and knowing their skills and abilities in translation; how they manage their personal and financial management, how they deal with customers, and what to do if things go wrong.